Relevance of technological innovation and entrepreneurship to biotechnology in Iran - Arabiun, Abolghasem; Shaye Sani, Mohammad Mahdi; Tayebnia, Mohammadreza; Zonoobi, Mojtaba (Researcher Bulletin of Medical Sciences, 2019)
One of the latest and most controversial areas of science is biotechnology. Genetic engineering concerns with the manipulation of DNA molecules to modify plants, animals and other creatures. Scientists are now able to isolate a gene or genome in an animal or plant to another one, based on the traits they want to transfer. The movement of a gene from a living creature to another one is called the recombinant DNA technology. The technology is developing rapidly. Regarding the specific features of biotechnology, opportunities are being created for the emergence of technological entrepreneurship projects in countries that have developed the logic science which provides the necessary capacity to establish connections to the international biotechnology network. This article seeks to find the relevance of technological innovation and entrepreneurship criteria to different technologies, including biotechnology. By improving sub-indicators of innovation and creating technological entrepreneurship units in businesses, we can increase the growth speed of their technologies. Moreover, some reports of global innovation indicators suggest the growth of Iran in technological areas from 2014 to 2017. This is due to the entering of technological entrepreneurship units in these areas, particularly biotechnology.